Beyond Personalist Virtue Ethics: Transcendental Anthropology and its Implications for Interpersonal Communication - Akrivou, Kleio; Fernández González, Manuel Joaquín (Frontiers in Communication, 2021)
There is a need of deeper understanding of what human beings are for facing adequately global challenges. The aim of this paper is to point to the possible contributions that transcendental anthropology would represent for complementing and expanding the valuable, but still incomplete solutions put forward by personalist virtue ethics to face these challenges. In particular, the question of the moral motivation and the complex relations between virtue and freedom are addressed, taking as starting point the understanding of the uniqueness of the personal act-of-being and the transcendentality of human freedom, which is in dialogue with human nature and society, but ultimately not subdued to none of them. Some implications of the transcendental anthropology in the field of interpersonal communication ethics are put forward.